Patent Foramen Ovale Closure in 2019 - Joel P Giblett; Omar Abdul-Samad; Leonard M Shapiro; Bushra S Rana; Patrick A Calvert (Interventional Cardiology: Reviews, Research, Resources)
Patent foramen ovale (PFO) is a common abnormality affecting between 20% and 34% of the adult population. For most people it is a benign finding; however, in some the PFO can open widely, enabling a paradoxical embolus to transit from the venous to arterial circulation, which is associated with stroke and systemic embolisation. Percutaneous closure of PFO in patients with cryptogenic stroke has been undertaken for a number of years, and a number of purpose-specific septal occluders have been marketed. Recent randomised controlled trials have demonstrated that closure of PFO in patients with cryptogenic stroke is associated with reduced rates of recurrent stroke. After a brief overview of the anatomy of a PFO, this review considers the evidence for PFO closure in cryptogenic stroke. The review also addresses other potential indications for closure, including systemic embolisation, decompression sickness, platypnoea–orthodeoxia syndrome and migraine with aura. It lays out the pre-procedural investigations and preparation for the procedure. Finally, it gives an overview of the procedure itself, including discussion of closure devices.